ANALISIS PENGARUH SERVICE EXCELLENCE TERHADAP KEPUASAN NASABAH PENABUNG PADA BPR SYARIAH HAJI MISKIN CABANG PAYAKUMBUH - Kevin Afrizal Saputra; Novera Martilova (Adisam Publisher, 2024)
The growth of saving customers from year to year fluctuates, the increase in the number of customers at BPR Syariah Haji Miskin Cabang Payakumbuh from year to year sometimes increases, sometimes decreases. Competition between BPRS Haji Miskin Cabang Payakumbuh with other BPRS and with Sharia Commercial Banks which are required to provide the best service in order to increase customer satisfaction and loyalty as well as improve the company's image. The aim of this research is to find out and analyze whether there is an influence and how much influence service excellence has on customer satisfaction of savers at BPR Syariah Haji Miskin Cabang Payakumbuh. The method used in this research is quantitative with data collection techniques, namely observation and questionnaires. Meanwhile, the data analysis technique uses correlation analysis, simple linear regression analysis, namely Y a + bx, t-test and determinant test (R2) to see the contribution of the independent variable to the dependent variable. From the research data obtained through simple linear regression, it was obtained that Y 12.319 + 0.358 (X) this figure shows a positive value so it is concluded that variable X has an influence on variable Y at BPR Syariah Haji Miskin Cabang Payakumbuh. The coefficient of determination (R2) value was 0.270. This means that there is an influence between variable X on variable Y of 27%. The results of this research show that the service excellence variable (X) has a positive influence on the customer satisfaction variable (Y), although the influence is weak with a small contribution, from this research the service excellence variable can be said to contribute and have a positive influence on customer satisfaction because it obtains good results. Significant.